Strategi Bandara I Gusti Ngurah Rai Bali dalam Mitigasi Bencana Gempa Bumi dan Tsunami - Sudiarta, I Ketut; Partama, I Gd Yudha; Arnawa, I Ketut; Vipriyanti, Nyoman Utari (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 10 No 2 (2023): October 2023, 2023)
This study aims to analyse the ability of I Gusti Ngurah Rai Airport to deal with catastrophic impacts brought by both earthquakes and tsunamis. It bases its analysis on twelve (12) indicators of earthquake and tsunami preparedness. It intends to develop strategies for dealing with these disasters to reduce the number of casualties. A questionnaire as its research instrument aided its data collection. The survey was carried out between a period of November – December 2022. The research is designed to combine qualitative and quantitative methods through a qualitative descriptive analysis approach, Likert analysis, SWOT and QSPM. The results show that I Gusti Ngurah Rai Airport Disaster Management Strategies for earthquakes and tsunamis fall in an outstanding category. Furthermore, it is emphasised that as a priority, a strategy that needs to be implemented by I Gusti Ngurah Rai Airport for earthquake and tsunami disaster mitigation is to strengthen disaster mitigation capabilities through twelve (12) earthquake and tsunami alert indicators by utilising advances in information technology. For future studies, it is hoped that new methods in disaster mitigation will be further explored. Keywords: airport; mitigation; earthquake; tsunami; victim   Abstrak Penelitian ini bertujuan menganalisis kemampuan Bandara I Gusti Ngurah Rai dalam menghadapi bencana gempa bumi dan tsunami berdasarkan 12 indikator siaga gempa dan tsunami serta menyusun strategi penanggulangan bencana tersebut agar tidak ada korban jiwa. Pengumpulan data menggunakan kuesioner sebagai instrumen penelitian dengan periode penelitian November – Desember 2022. Rancangan penelitian menggunakan kombinasi metode kualitatif dan kuantitatif, melalui pendekatan analisis deskriptif kualitatif, analisis Likert, SWOT dan QSPM. Hasil penelitian menunjukkan kemampuan Bandara I Gusti Ngurah Rai dalam mitigasi bencana gempa bumi dan tsunami berada pada kategori sangat baik berdasarkan 12 indikator gempa bumi dan tsunami. Strategi prioritas yang dapat diimplementasikan Bandara I Gusti Ngurah Rai untuk mitigasi bencana gempa bumi dan tsunami adalah penguatan kemampuan mitigasi bencana gempa bumi dan tsunami melalui 12 indikator siaga gempa bumi dan tsunami dengan memanfaatkan kemajuan teknologi informasi. Untuk penelitian ke depan, diharapkan metode-metode baru akan dieksplorasi lebih lanjut. Kata kunci: bandara; mitigasi; gempa bumi; tsunami; korban